Cu loading alters expression of non-IRE regulated, but not IRE regulated, Fe dependent proteins in HepG2 cells - Fosset, Cédric; Danzeisen, Ruth; Gambling, Lorraine; McGaw, Brian A.; McArdle, Harry J. (Journal of inorganic biochemistry, 2009)
This paper investigates the extent to which Cu loading influences Fe levels in HepG2 cells and the effect on proteins regulated by Fe status. Cu supplementation increased Cu content 3-fold, concomitant with a decrease in cellular Fe levels. Intracellular levels of both transferrin (Tf) and ceruloplasmin (Cp) protein rose in parallel with increased secretion into the culture media. There was no increase in mRNA levels for either protein. Rather, our data suggested increased translation of the mRNA. The increase was not reflected in total protein synthesis, which actually decreased. The effect was not a generalised stress or cell damage response, since heat shock protein 70 levels and lactate dehydrogenase secretion were not significantly altered. To test whether the Cu effect could be acting though the decrease in Fe levels, we measured transferrin receptor (TfR) levels using 125I labeled Tf and mRNA analysis. Neither protein nor mRNA levels were changed. Neither was the level of ferroportin mRNA. As a positive control, Fe chelation increased Tf and Cp secretion significantly, and TfR mRNA levels rose 2-fold. We excluded the possibility that the increased Cp or Tf could provide the required substrate to stimulate Fe efflux, and instead demonstrate that Cu can substitute for Fe in the iron regulatory protein – iron responsive element regulation mechanism.